1998
DOI: 10.3354/meps166211
|View full text |Cite
|
Sign up to set email alerts
|

Predation on postlarvae and juveniles of the shore crab Carcinus maenas:importance of shelter, size and cannibalism

Abstract: Settlement and early juvenile stages are considered a bottleneck in the life history of many epibenthic organisms because of high predation mortality. Nursery habitats may play an irnportant role in mitigating settlement and post-settlement mortality by providing refuge from predation. We examined these relationships in postlarvae and early juvenile stages of the shore crab Carcinus maenas L. in laboratory and field tethering experiments. We studied habitat and size related habitat mortality using postlarvae a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
128
1
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(143 citation statements)
references
References 36 publications
5
128
1
3
Order By: Relevance
“…and Sainte-Marie, 1997;Moksnes et al, 1997Moksnes et al, , 1998 . This is probably due to uniform size within a cohort.…”
Section: Discussionmentioning
confidence: 99%
“…and Sainte-Marie, 1997;Moksnes et al, 1997Moksnes et al, , 1998 . This is probably due to uniform size within a cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Hedvall et al (1998) showed that megalopae of C. maenas avoid unstructured substrates such as sand. In these types of substrate the predation rates are very high, reaching, according to Moksnes et al (1998), more than 80% in 2 days. The synthetic fibbers of the collector surface provide shelter to prevent predation and trap organic matter that may further enhance settlement.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors showed that megalopae of several species prefer structurally complex substrates, which provide shelter (e.g. O'Connor, 1993;Eggleston & Armstrong, 1995;Hedvall et al, 1998;Moksnes et al, 1998;Stevens & Kittaka, 1998). These substrates include vegetation (Bostro¨m & Bonsdorff, 1997) and shelly gravel .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Premature releases would include larvae still displaying planktonic behavior, exposing them to greater predation risk (Johns and Mann, 1987;Dittel et al, 1996;Moksnes et al, 1997Moksnes et al, , 1998 as well as reducing the effectiveness of the restocking due to the transport of larvae away from the focal areas. Excessively late releases, on the other hand, entail extensive losses through cannibalism within larviculture tanks (Quinitio and Parada-Estepa 1999), as well as increased rearing costs.…”
Section: Introduction *mentioning
confidence: 99%